TWO CASES OF IMMUNE CHECKPOINT INHIBITOR INDUCED THYROIDITIS FROM UNIVERSITY MALAYA MEDICAL CENTRE - Jalal, Fadzliana Hanum; Ibrahim, Luqman; Lim, Quan-Hziung; Ratnasingam, Jeyakantha; Paramasivam, Sharmila Sunita; Vethakkan, Shireene Ratna; Lim, Lee-Ling (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Immune checkpoint inhibitor (ICPi) is a known but rare cause of thyroiditis. However, there is a lack of local evidence due to scarce availability of ICPi as a novel treatment for oncology patients. We presented two cases of thyroiditis following treatment with PD-1 checkpoint inhibitors (anti-PD-1) namely pembrolizumab and cemiplimab. RESULTS Case A was a 49-year-old female who received pembrolizumab for recurrent metastatic HER2-negative breast cancer after mastectomy, radiotherapy and chemotherapy. Her thyroid function test at baseline was free T4 17.2pmol/L (normal range: 11.5-22.7) and TSH 0.63 mIU/L. After 3 weeks of pembrolizumab, she had biochemical hyperthyroidism (free T4 45.5 pmol/L; TSH <0.01 mIU/L), mildly raised thyroid stimulating immunoglobulins (0.94 IU/L; normal range: <0.55) and a normal thyroid ultrasound. She was treated with tapering dose of carbimazole 20mg daily but developed hypothyroidism (free T4 4.2 pmol/L; TSH 61.55 mIU/L) 5 weeks later while on carbimazole 5mg daily. She remained clinically and biochemically euthyroid with levothyroxine 100 mcg daily. Case B was a 63 year-old male who received cemiplimab for non-small-cell lung cancer with brain metastases after stereotactic brain surgery. He was euthyroid at baseline (free T4 -NA; TSH 0.55 mIU/L). After 3 months of cemiplimab, he had deranged thyroid function test (free T4 23.9 pmol/L; TSH 0.03 mIU/L), which progressed to biochemical hypothyroidism (free T4 7.5 pmol/L; TSH 49.61 mIU/L) 10 months later. He was treated with levothyroxine 25 mcg daily with latest free T4 15.4pmol/L and TSH 18.12 mIU/L CONCLUSION Thyroid function test screening is required for all patients undergoing treatment with ICPi. Clinicians need to have a high index of suspicion for ICPi-associated thyroid dysfunction which can be appropriately treated with medical therapy